2020
DOI: 10.1094/mpmi-06-19-0174-r
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Metabolomic Analysis of Setaria viridis Roots Colonized by Beneficial Endophytic Bacteria

Abstract: Over the past decades, crop yields have risen in parallel with increasing use of fossil fuel–derived nitrogen (N) fertilizers but with concomitant negative impacts on climate and water resources. There is a need for more sustainable agricultural practices, and biological nitrogen fixation (BNF) could be part of the solution. A variety of nitrogen-fixing, epiphytic, and endophytic plant growth–promoting bacteria (PGPB) are known to stimulate plant growth. However, compared with the rhizobium-legume symbiosis, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 92 publications
1
11
1
Order By: Relevance
“…These -omics methods can be complemented by other approaches, such as confocal microscopy, which, after inoculation of a strain into an axenic plant, makes it possible to verify that the strain is indeed an endophyte and to identify the tissues it colonizes (Bünger et al, 2020). Agtuca et al (2020) combined confocal and fluorescence imaging with in situ metabalomics to discover the metabolites that are over-expressed in plant tissues colonized by an endophytic bacterium. The future challenge in plant endophyte research is, however, not only to master and combine advanced tools, but also to link research questions to conceptual frameworks (Saikkonen et al, 2020).…”
Section: Methodological Challenges and Limitations To Study Endophytesmentioning
confidence: 99%
“…These -omics methods can be complemented by other approaches, such as confocal microscopy, which, after inoculation of a strain into an axenic plant, makes it possible to verify that the strain is indeed an endophyte and to identify the tissues it colonizes (Bünger et al, 2020). Agtuca et al (2020) combined confocal and fluorescence imaging with in situ metabalomics to discover the metabolites that are over-expressed in plant tissues colonized by an endophytic bacterium. The future challenge in plant endophyte research is, however, not only to master and combine advanced tools, but also to link research questions to conceptual frameworks (Saikkonen et al, 2020).…”
Section: Methodological Challenges and Limitations To Study Endophytesmentioning
confidence: 99%
“…Noteworthily, the previous studies have shown that the nitrogen fixation ability and the changes of nitrogen in plants are also affected by soil fertility [51,52], soil microorganisms [53,54] or metal elements [55]. We studied the change of elevated CO 2 content as the main factor but did not verify or discuss the influence of other factors on nitrogen metabolism of Masson pine under the same condition.…”
Section: Enzyme Activities and Gene Expression Response To Co 2 Stressmentioning
confidence: 99%
“…H. seropedicae SmR1 is a well-studied endophytic bacterium that colonizes several plants, including maize, wheat, and Setaria. Recently, in situ metabolomic profiling of S. viridis roots colonized by SmR1 demonstrated that inoculation induced a wide variety of plant metabolic changes, including those affecting nitrogen and phytohormone levels (15). Thus, similar to many other, better-studied plant-microbe associations, PGPB inoculation appears to profoundly affect the metabolism of its host.…”
mentioning
confidence: 95%